2012
DOI: 10.1016/s1995-7645(12)60115-1
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes and practices towards avian influenza A (H5N1) among Cambodian women: A cross–sectional study

Abstract: We report a satisfactory level of positive attitudes, and moderate level of knowledge and practices related to HPAI among Cambodian women. Raising KAPs through television, radio and other medias may be more efficient than using usual information, education and communication materials to prevent HPAI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 25 publications
2
10
4
Order By: Relevance
“…This finding is a little bit lower than the finding of similar study done among Cambodian women, which showed that more than half (57.3%) of respondents suggested that modern medicine available for curing HPAI [16].In general the finding of our study shows that the level of participants' awareness on HPAI is low which contradicts with the studies done in Italy and china reporting high level of awareness [17,18]. This gap could be explained by the fact that the level of literacy among our respondents and the media coverage on HPAI is poor.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…This finding is a little bit lower than the finding of similar study done among Cambodian women, which showed that more than half (57.3%) of respondents suggested that modern medicine available for curing HPAI [16].In general the finding of our study shows that the level of participants' awareness on HPAI is low which contradicts with the studies done in Italy and china reporting high level of awareness [17,18]. This gap could be explained by the fact that the level of literacy among our respondents and the media coverage on HPAI is poor.…”
Section: Discussioncontrasting
confidence: 69%
“…However, transmission by direct contact with ill person and eating raw poultry meat and egg products is responded by few participants as it is compared to other studies. For instance, the result of a cross-sectional study conducted among Cambodian women showed that majorities' response on the modes of transmission of AI is, direct contact with sick or dead birds and followed by airborne transmission which showed a better awareness as compared with our study finding [16]. This difference might be the difference in educational level among the two study groups.…”
Section: Discussioncontrasting
confidence: 51%
“…Homayounimehr et al (2010) and Soltanialvar et al (2010) have shown that the Iranian isolates possessed amino acid leucine (L) at position 226 instead of glutamine (Q) at the receptor binding site of haemagglutinins (HA) which is similar to A/Quail/HongKong/G1/97 and two human isolates: A/HK/1073/99, A/HK/1074/99 [35][36][37]18] . Amino acid differences in the receptor binding sites of HAs have been shown to be associated with differences in receptor binding specificity [22] .…”
Section: Discussionmentioning
confidence: 99%
“…A KAP survey of poultry handling behavior among villagers in rural Cambodia revealed that despite high awareness and widespread knowledge about AI and personal protection measures, most rural Cambodians still often practice at-risk poultry handling. Intervention programs must include feasible options for resource-poor settings that have limited materials for personal protection (water, soap, rubber gloves, and masks) and must offer farmers alternative methods to safely work with poultry on a daily basis [185,186].…”
Section: Knowledge Attitudes and Practices (Kap) Of Poultry Workers mentioning
confidence: 99%
“…The internet (76.92%), television (67.56%), and newspapers (56.26%) were the main sources for food company employees obtaining information, and varied by demographic variables [190]. Radio, leaflets/booklets, school students and village health volunteers were found to be the most effective sources in increasing knowledge of rural dwellers [186].…”
Section: Knowledge Attitudes and Practices (Kap) Of Poultry Workers mentioning
confidence: 99%